Effects of orally administered ovine serum immunoglobulin in the normal and Salmonella enteritidis-challenged growing rat. : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Nutrition at Massey University, Palmerston North, New Zealand - Balan, Prabhu; Balan, Prabhu (Massey University, 2011)
Immunoglobulins (Ig) are the primary anti-infective component of plasma, colostrum and breast milk. They are the specialized glycoproteins that protect the body from harmful bacteria, viruses and other environmental pathogens by either binding to them or by forming an encapsulating barrier. The development of antimicrobial and immunomodulatory products from natural sources for dietary supplementation in both animals and humans is an active area of research. Purified Ig from sheep plasma (ovine serum Ig) is one such candidate product. Based on the results of the numerous background growth studies of others, the objectives of this study were to determine whether orally administered ovine serum Ig affected growth performance, digestive organ weights, gut morphology, immunity, the gut microbiota, goblet cell numbers, mucin gene expression and digesta mucin protein contents in the growing rat. The study also sought to understand whether orally administered ovine serum Ig prevented or lessened the negative effects of Salmonella enteritidis ATCC 13076 (a pathogen) in the S. enteritidis−challenged growing rat. The presence of ingested intact Ig in different parts of the digestive tract was also determined. Investigations were undertaken in normal and S. enteritidis−challenged Sprague-Dawley male growing rats. Diets were iso-caloric and had similar protein and amino acid contents. The diets were fed for 21 days (for non-challenged rats) and for 18 days (for the challenged rats). An ovine Ig fraction improved food conversion efficiency, the weights of several digestive organs and gut histology. Compared with spray-drying, a freeze-drying procedure preserved a higher degree of immunological activity. In immunity studies, an ovine Ig fraction selectively enhanced (P < 0.05) various indices of immune function such as phagocytic acitivity, lymphocyte proliferation and gut and plasma antibodies. In microbiolgical studies, the number of lactobacilli in the gut were increased (P < 0.05) by feeding the ovine Ig. Ovine Ig also influenced the transcription and translation of gut mucin protein as evidenced by increased (P < 0.05) mucin gene expression and digesta mucin protein concentrations as well as an increased goblet cell count. After gavaging with S. enteritidis, the rats fed the IOI (inactivated ovine Ig) and BD (basal diet) diets grew considerably more slowly (growth declined) than the challenged rats fed the FDOI (freeze-dried ovine Ig) diet and the latter rats showed no sign of infection. The villus length, crypt depth, villus:crypt ratio and villus surface area (VSA) of the duodenum and jejunum were generally greater (P < 0.05) in rats challenged with S. enteritidis and receiving the FDOI diet compared to either the unchallenged rats fed the BD diet (except duodenal and jejunal VSA) or the challenged rats fed the BD or IOI diets. Several measures of immune modulation were affected as was the bacterial composition of the gut microflora. The ileal and colonic digesta for the FDOI-fed rats had higher (P < 0.05) numbers of goblet cells and higher (P < 0.05) digestive luminal mucin protein concentrations than the challenged rats fed either the BD- or IOI-supplemented diets. Intact ovine Ig were detected in the luminal contents from the stomach through to the colon in the growing rat fed orally with ovine Ig fraction. The amounts (percentages of digesta dry matter) of intact ovine Ig for rats fed the FDOI diet were 2.17%, 3.12%, 5.31%, 2.03% and 5.76% for stomach chyme, duodenal, jejunal, ileal and colonic digesta respectively. Overall, the accumulated amount was 18.4%, which indicates the presence of a high level of active material throughout the digestive tract. In conclusion, purified ovine Ig improves growth of healthy rats and protects against enteric infection by immunomodulation, mucin protein and/or modification of commensal microbial composition. The results contribute to knowledge of how orally administered ovine Ig can modulate and enhance key indicators of gut function and overall growth performance in the growing rat.
Keywords: Dietary supplements; Rat growth; Rat diet; Lactobacillus johnsonii; Mucin